Nivel de conocimiento tributario y formalización de los pequeños empresarios de aserrío de la ciudad de Contamana año 2022 - Tuesta Flores, Kiko (2023)
The research aimed to determine the relationship between the level of tax knowledge and formalization of small sawmill entrepreneurs in the city of Contamana year 2022, which was inclined to a study of applied type, descriptive level – correlational and non-experimental design, including as a study population 75 small entrepreneurs, those who were applied the survey technique and the questionnaire as an instrument. Later in the results it was possible to determine that the level of tax knowledge of small sawmill entrepreneurs in the city of Contamana is medium (29%) because they have almost never attended any talk or orientation on how to tax; in addition, he is sometimes aware of the tax benefits offered by the State. On the other hand, formalization is classified as low (33%), since sometimes you know under what tax regime the commercial activity of your company is; Also, that accounting books are almost never duly legalized by a notary. In conclusion, the relationship between the level of tax knowledge and formalization of small sawmill entrepreneurs in the city of Contamana year 2022 is considerable positive, since the correlation statistic showed a significance of 0.01 and a coefficient of 0.793.